Investing in our future: an evaluation of the national rollout of the Home Interaction Program for Parents and Youngsters (HIPPY): final report to the Department of Education, Employment and Workplace Relations - Liddell, M (Department of Education, Employment and Workplace Relations, 2011)
A national evaluation of the Home Interaction Program for Parents and Youngsters (HIPPY), a combined home and centre-based early childhood enrichment program that supports parents in their role as their child’s first teacher, has found significant benefits for parents and children. The effectiveness of HIPPY was evaluated by means of a two-year longitudinal, quasi-experimental research design that involved a comparison group drawn from the Longitudinal Study of Australian Children using propensity score matching.
Keywords: Children -- Early childhood; Childhood and child development; Children; Early childhood; Childhood and child development